Rejuvenation of the nata-organism (Acetobacter Xylinum) - Teruel, Sylvia Rose Luzette T.
A method of recycling the starter (Acetobacter xylinum) for nata making was studied. The rejuvenating effect of dextrose and sucrose as carbon sources and dihydrogen ammonium phosphate and ammonium sulfate was compared. Results showed that dextrose and dihydrogen ammonium phosphate are better rejuvenators than sucrose and ammonium sulfate. It was found necessary to enrich the media with carbon and nitrogen sources if the mother liquor is to be recycled. It has been observed that yield and thickness of the nata produced from the medium without any enrichment decreased as the mother liquor was recycled. Whereas thicker and heavier nata were produced from the media enriched with dextrose and dihydrogen ammonium phosphate as the mother liquor was continuously recycled. Recycling was done two times. Among the combinations tested, the "10% dextrose & 0.5% dihydrogen ammonium phosphate" was found to be the best that could restore the normal growth and activity of Acetobacter xylinum.